Medical students’ intention to integrate digital health into their medical practice: A pre-peri COVID-19 survey study in Canada - Guy Paré; Louis Raymond; Marie-Pascale Pomey; Geneviève Grégoire; Alexandre Castonguay; Antoine Grenier Ouimet (Digital Health, 2022)
Objective We aimed to explore the factors that influence medical students’ intention to integrate dHealth technologies in their practice and analyze the influence of the COVID-19 pandemic on their perceptions and intention. Methods We conducted a two-phased survey study at the University of Montreal's medical school in Canada. The study population consisted of 1367 medical students. The survey questionnaire was administered in two phases, that is, an initial survey (t 0 ) in February 2020, before the Covid-19 pandemic, and a replication survey (t 1 ) in January 2021, during the pandemic. Component-based structural equation modeling (SEM) was used to test seven research hypotheses. Results A total of 184 students responded to the survey at t 0 (13%), whereas 138 responded to the survey at t 1 (10%). Findings reveal that students, especially those who are in their preclinical years, had little occasion to experiment with dHealth technologies during their degree. This lack of exposure may explain why a vast majority felt that dHealth should be integrated into medical education. Most respondents declared an intention to integrate dHealth, including AI-based tools, into their future medical practice. One of the most salient differences observed between t 0 and t 1 brings telemedicine to the forefront of medical education. SEM results confirm the explanatory power of the proposed research model. Conclusions The present study unveils the specific dHealth technologies that could be integrated into existing medical curricula. Formal training would increase students’ competencies with these technologies which, in turn, could ease their adoption and effective use in their practice.